2009
DOI: 10.1007/s10517-009-0572-5
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation-Induced Genomic Instability in CHO cells Is Followed by Selection of Radioresistant Cell Clones

Abstract: The DNA comet assay (neutral version) showed that irradiation of CHO cells in a dose of 1 Gy (gamma-radiation, (60)Co) is followed by an increase in the degree of DNA fragmentation. These changes were observed immediately after irradiation and on days 7-21. On days 2-4 and 23-28 after irradiation, the degree of DNA fragmentation in the descendants of irradiated cell did not differ from that in control samples. The increase in the degree of DNA fragmentation on days 7-21 probably results from induction of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Indeed, we did not observe increased rates of γН2АХ foci at passages 3 and 5 after irradiation, implying that irradiated MSCs (at least at the doses used here) do not transmit the residual γH2AX foci through the cell divisions, as described by Vaurijoux et al [ 71 ]. At the same time the observed high rates of γН2АХ foci in the progeny (passages 8 and 11) of 1000 mGy-exposed cells is consistent with radiation-induced genome instability [ 72 , 73 ] or accelerated cellular senescence [ 74 , 75 ]. Genome instability and senescence are not necessarily linked.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, we did not observe increased rates of γН2АХ foci at passages 3 and 5 after irradiation, implying that irradiated MSCs (at least at the doses used here) do not transmit the residual γH2AX foci through the cell divisions, as described by Vaurijoux et al [ 71 ]. At the same time the observed high rates of γН2АХ foci in the progeny (passages 8 and 11) of 1000 mGy-exposed cells is consistent with radiation-induced genome instability [ 72 , 73 ] or accelerated cellular senescence [ 74 , 75 ]. Genome instability and senescence are not necessarily linked.…”
Section: Discussionmentioning
confidence: 53%
“…GI is associated with both tumour aggressivity and progression 132 , as well as RR 133 , 134 , though only a few studies have linked it to hypoxia-induced RR. The connection between GI and RR is mostly indirect, with GI thought to lead to the development of radioresistant clones following periods of chromosomal rearrangements 135 , 136 . A number of studies have shown development of GI in hypoxia 66 , a feature particularly relevant for tumours lacking functional p53 as is common in many hypoxic cancers, as apoptosis will be less likely to occur 137 .…”
Section: Reprogramming Of the Ddrmentioning
confidence: 99%
“…Active oxygen species are the main cause of the destructive effect of radiation [14]. Radiation exposure can cause delayed effects because of the genome instability emergence [1]. Genetically unstable cell strains can cause malignant transformation of normal cells and emergence of radiation-resistant cancer cell clones [1].…”
Section: Resultsmentioning
confidence: 99%
“…Radiation exposure can cause delayed effects because of the genome instability emergence [1]. Genetically unstable cell strains can cause malignant transformation of normal cells and emergence of radiation-resistant cancer cell clones [1]. Genetically unstable cells are characterized by hyperproduction of ROS, presumably generated by the mitochondria [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation